2017
DOI: 10.1017/s0140525x17001704
|View full text |Cite
|
Sign up to set email alerts
|

Live theatre as exception and test case for experiencing negative emotions in art

Abstract: Distancing and then embracing constitutes a useful way of thinking about the paradox of aesthetic pleasure. However, the model does not account for live theatre. When live actors perform behaviors perceptually close to real life and possibly really experienced by the actors, audiences may experience autonomic reactions, with less distance, or may have to distance post-experiencing/embracing their emotions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…The greater the participants’ understanding of arts activities, the stronger their aesthetic emotions [ 69 ]. Creators and performers who craft vivid and lively artistic images demonstrate their understanding of art and elicit aesthetic and emotional experiences [ 70 ]. Relevant studies have suggested that experiencing aesthetic beauty and seeking emotional resonance are crucial reasons for visiting art museums [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…The greater the participants’ understanding of arts activities, the stronger their aesthetic emotions [ 69 ]. Creators and performers who craft vivid and lively artistic images demonstrate their understanding of art and elicit aesthetic and emotional experiences [ 70 ]. Relevant studies have suggested that experiencing aesthetic beauty and seeking emotional resonance are crucial reasons for visiting art museums [ 71 ].…”
Section: Discussionmentioning
confidence: 99%